Comparative study of elastic properties of marl and limestone layers in the Eagle Ford formation - Jiang, Shuxian; Mokhtari, Mehdi; Song, Jinze (Frontiers in Earth Science, 2023)
Eagle Ford Formation has significant heterogeneity due to the existence of marl and interbedded limestone layers. The objective of this paper is to study the elastic properties of different layers in the Eagle Ford Formation. To achieve the goal, the relationships between compressional and shear velocities in marl and limestone layers were investigated in two representative Eagle Ford wells. These empirical equations can be used to estimate shear velocities in the Eagle Ford wells without sufficient well log data. Moreover, correlations between elastic properties and GR were obtained. Among all layers in the Eagle Ford Formation, marl layers of the lower Eagle Ford have the lowest averaged values of compressional velocity, shear velocity and dynamic Young’s modulus, while the limestone layers of the upper Eagle Ford have the highest averaged values of these three elastic parameters. In addition, the effect of elastic properties of shale layers on the aspect ratio of unconfined and confined fractures were evaluated. The influence of Young’s modulus contrast of shale layers on the aspect ratio of confined fractures was remarkable.